Community Pharmacies Mood Intervention Study (CHEMIST): feasibility and external pilot randomised controlled trial protocol - Littlewood, Elizabeth (Pilot Feasibility Stud, 2019)
FEASIBILITY STUDY: Objectives: a. Refine a bespoke enhanced support intervention (ESI) (including self-help materials, intervention manual and training) for implementation by community pharmacy (CP) staff to people with sub-threshold depression and long-term conditions (LTCs) based upon evidence-supported interventions in primary care. b. Develop and refine study procedures (recruitment strategies and set up, screening, participant recruitment, assessment, suitability of outcome measures and data collection procedures) for testing in the pilot study phase. Design: A case series/qualitative study Setting: UK community pharmacy Population: Adults with long-term health conditions who screen-positive for depression but who do not reach the threshold for DSM IV Moderate Depressive disorder Intervention: Enhanced support intervention (ESI) delivered by an appropriately trained community pharmacy team member involving four to six sessions over four months. ESI is a modified form of an intervention within the collaborative care framework for sub-threshold depression validated in previous studies in UK primary care which appears suitable for implementation in community settings. Sample size: 20–30 participants Outcomes: Study implementation (recruitment and attrition rates), quality of data collection at baseline and 4 months and ESI adherence (number of contacts, DNA and drop out) as per objectives 1a/b Qualitative evaluation: Semi-structured interviews with up to 10 participants and ESI facilitators and focus group(s) (range of pharmacy staff n = 8–10) will be conducted to explore the acceptability of the intervention and feasibility of the study, training and study procedures. EXTERNAL PILOT STUDY: Objectives: a. Quantify the flow of participants (eligibility, recruitment and follow-up rate). b. Evaluate proposed recruitment, assessment and outcome measure collection methods. c. Examine the delivery of the enhanced support intervention in a community pharmacy setting (intervention uptake, retention and dose) to inform process evaluation. d. Process evaluation, using semi-structured interviews with participants across a range of socio-economic settings, and pharmacy staff to explore the acceptability of the ESI within community pharmacy, elements of the intervention that were considered useful (or not) and appropriateness of study procedures. Design: Pilot randomised controlled trial, including a prospective economic and qualitative evaluation Setting: As above Population: As above Intervention: As above with adaptations post feasibility study Comparator: Usual care Sample size: 100 participants Outcomes: Data will be used to estimate recruitment, intervention delivery and study completion rates as per objectives 2a–d. Definitive estimates of the effectiveness of ESI will not be made. Primary outcome: Depression severity (Patient Health Questionnaire 9) at four months. Secondary outcomes: Patient acceptance, uptake and attrition. ICD10 depression status, anxiety (GAD 7), health-related quality of life (SF-12v2) and health-state utility (EQ5D 3L) will be measured at four months. Economic evaluation: The incremental cost per QALY will be calculated from both the NHS and societal perspective. Process evaluation: Using mixed methods, potential mediators/moderators of the intervention, the acceptability (to participants and pharmacy staff), barriers and facilitators to the use of ESI in community pharmacy, and impact on usual practice will be examined. Semi-structured interviews with approximately 30 study participants, 20 pharmacy staff and eight GPs near participating pharmacies will be conducted. TRIAL REGISTRATION: ISRCTN: ISRCTN11290592 Protocol version number: Version 4.1 (dated 16th January 2018) Study Sponsor Tees Esk and Wear Valleys NHS Foundation Trust ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40814-019-0457-y) contains supplementary material, which is available to authorized users.